Non-HDL cholesterol paradox and effect of underlying malnutrition in patients with coronary artery disease: A 41, 182 cohort study. Issue 3 (March 2022) - Wang, Bo; Guo, Zhaodong; Li, Huanqiang; Zhou, Ziyou; Lu, Hongyu; Ying, Ming; Mai, Ziling; Yu, Yaren; Yang, Yongquan; Deng, Jingru; Chen, Jiyan; Tan, Ning; et al.
Summary: Background & aims: Non-high-density lipoprotein cholesterol (non-HDL-C) and low-density lipoprotein cholesterol (LDL-C) were established as the target for blood lipid management among patients with coronary artery disease (CAD). Previous study reported a negative relation between baseline LDL-C levels and long-term prognosis. However, the association between baseline non-HDL-C concentration and clinical outcomes is unknown. Methods: A total of 41, 182 CAD patients admitted to Guangdong Provincial People's Hospital in China were included in this study from January 2007 to December 2018 and divided into two groups (non-HDL-C < 2.2 mmol/L, n = 3236; non-HDL-C ≥ 2.2 mmol/L, n = 37, 946). The Kaplan–Meier method, Cox regression analyses and restricted cubic splines were used to assess the association between non-HDL-C levels and long-term all-cause mortality. Results: The overall mortality was 12.74% (n = 5247) over a median follow-up period of 5.20 years. Kaplan–Meier analysis showed that low non-HDL-C levels were paradoxically associated with a worse prognosis. After adjustment for baseline confounders (e.g., age, sex and comorbidities, etc.), multivariate Cox regression analysis revealed that low non-HDL-C levels (<2.2 mmol/L) were not significantly associated with all-cause mortality (adjusted HR, 1.03; 95% CI, 0.93–1.14). After adjustment for nutritional status, the risk of all-cause mortality in patients with low non-HDL-C levels decreased (adjusted HR, 0.86; 95% CI, 0.78–0.95). In the final multivariate Cox model adjusting for full covariates, low non-HDL-C level was related to better prognosis (adjusted HR, 0.88; 95% CI, 0.80–0.98). Conclusion: This study found a paradoxical association between baseline non-HDL-C concentration and long-term all-cause mortality. Malnutrition mainly mediates to the non-HDL-C paradox. Elevated non-HDL-C concentration is still a risk factor of long-term all-cause mortality after considering nutritional status.